Study the ultrastructure changes in the liver of mice post infection with Listeria monocytogenes: Zainab I. Ibrahim1 Moutaz A. W. Abdul –Mounam2 and Laith A. M. Alsufi3 - Ibrahim, Zainab I. (The Iraqi Journal of Veterinary Medicine, 2017)
Listeria monocytogenes has important medical health infection in human and animals. The present study aimed to investigate the significant ultrastructure changes occurred in liver post-infection by pathogenic strain of Listeria monocytogenes. Twenty-six mice of both sexes divided into two groups; 1st group (n=21) infected with 0.2 ml (2x109 CFU/ml) of Listeria monocytogenes I/P and 2nd group (n=5) served as negative control group, all animal of both groups sacrificed at 2, 4, 6 and 24 hours post infection (7 mice for each time of infected group). The histopathology of liver tissues post infection revealed degenerative changes and severe necrosis in hepatic lobules exclusively at 6 and 24 hours also there were significant ultrastructure changes of hepatocytes; degeneration and necrosis of hepatocytes appeared at 2 hours post infection.